Answer:
-18 = -18 It is true.
Step-by-step explanation:
-6 -1.5(4b+8) = 3(-6 -2b)
-6 -6b - 12 = -18 -6b
-6b -18 = -18 -6b
+6b +6b
-18 = -18
It is true.
Answer:
1. 4x = 15
2. 4(n - 3) = 24
3. 2n + 5 = 13
4. (3/4)n = 9
5. 6x - 4 = 8
Step-by-step explanation:
this should be correct. hope this helps!
i hope it is helpful ti youu
Answer:
c^6
Step-by-step explanation:
So, c is the same as c^ 1 ... therefore
c^5 x c
= c^5 x c^1
When we multiply two numbers with same base and different exponent, we add the exponents which in this case as 5 and 1
So c^5 x c^1
= c^(5+1)
= c^6
This is the simplest form